THE RELATIONSHIP BETWEEN WORKING HOURS, WORK DURATION, AND LIGHTING INTENSITY ON EYE FATIGUE AMONG TAILORS IN TANJUNG MULIA HILIR SUBDISTRICT, MEDAN CITY - Ginting, Tarianna; Tampubolon, Jenni; Suvina, Vivi; Siagian, Masryna; Sihotang, Widya Yanti (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Inadequate lighting and long working hours are common occupational health issues faced by tailors in Tanjung Mulia Hilir Village, Medan City. These unfavorable conditions may contribute to eye fatigue, reduced concentration, decreased productivity, and a higher risk of sewing errors. Prolonged work duration without adequate rest also increases the risk of health complaints such as headaches, back pain, and vision problems. This study aimed to examine the relationship between work duration, work experience, and lighting intensity on the incidence of eye fatigue among tailors. The study employed a quantitative analytic method with a cross-sectional design, involving 60 respondents selected through total sampling. Data were collected through questionnaires and direct measurements of lighting levels. The results showed that 19 respondents (31.7%) had adequate lighting, while 41 (68.3%) worked under inadequate lighting conditions. A total of 16 respondents (26.7%) experienced eye fatigue. Bivariate analysis revealed a p-value of 0.00, indicating a significant relationship between work duration and lighting intensity with eye fatigue. It is recommended that workplace lighting conditions and working hours be improved to reduce the risk of visual fatigue.